Cardiac Lymphoma Diagnosed by Multi-Modality Imaging: A Case Report - Yang, Dayan; Wu, Tangna; Gao, Lini; Liu, Lili; Liu, Fujin; Jing, Xiangxiang (Frontiers in Cardiovascular Medicine, 2022)
We present a case of a 79-year-old female, who had a cardiac mass detected by conventional echocardiography, diagnosed as cardiac lymphoma by myocardial contrast echocardiography and confirmed by pathological result.Cardiac lymphoma is very rare. By retrospectively analyzing the clinical symptoms and ultrasonic manifestations of this patient, we have summarized some experience. Although conventional echocardiography can find space-occupying lesions, it is difficult to determine malignant and benign tumors. Myocardial contrast echocardiography could directly reflect the location, shape, size of the lesions and its relationship with the surrounding tissues, also could objectively evaluate the blood supply in the space-occupying lesions. It has great application value for the qualitative diagnosis of the space-occupying lesions, and can provide an important basis for clinical treatment and decision-making. Avoidance of cardiovascular angiography,cardiac surgery and other diagnostic methods leads to less trauma for patients.